Optical and spin coherence of Er spin qubits in epitaxial cerium dioxide on silicon - Jiefei Zhang; Gregory D. Grant; Ignas Masiulionis; Michael T. Solomon; Jonathan C. Marcks; Jasleen K. Bindra; Jens Niklas; Alan M. Dibos; Oleg G. Poluektov; F. Joseph Heremans; Supratik Guha; David D. Awschalom (npj Quantum Information)
Abstract Robust spin-photon interfaces with optical transitions in the telecommunication band are essential for quantum networking technologies. Erbium (Er) ions are the ideal candidate with environmentally protected transitions in telecom-C band. Finding the right technologically compatible host material to enable long-lived spins remains a major hurdle. We introduce a new platform based on Er ions in cerium dioxide (CeO2) as a nearly-zero nuclear spin environment (0.04%) epitaxially grown on silicon, offering silicon compatibility for opto-electrical devices. Our studies focus on Er3+ ions and show a narrow homogeneous linewidth of 440 kHz with an optical coherence time of 0.72 μs at 3.6 K. The reduced nuclear spin noise enables a slow spin-lattice relaxation with a spin relaxation time up to 2.5 ms and an electron spin coherence time of 0.66 μs (in the isolated ion limit) at 3.6 K. These findings highlight the potential of Er3+:CeO2 platform for quantum networks applications.